2014
DOI: 10.1177/0333102414523339
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion patterns in migraine with aura

Abstract: Migraine aura is usually associated with a perfusion deficit not limited to a specific vascular territory, and only a moderate increase of TTP. Thus, hypoperfusion restricted to a single vascular territory in combination with a marked increase of TTP or MTT may be regarded as atypical for migraine aura and suggestive of acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 33 publications
7
51
0
Order By: Relevance
“…From a methodologic point of view, we excluded the transition parameters (TTP and MTT) from our perfusion analysis. Our findings were in line with those of Förster et al, 32 who demonstrated that perfusion abnormalities in patients with MwA are predominantly substantiated by CBF and CBV changes. TTP analysis of the cerebellar hemispheres is hampered by variant vertebral artery configurations that directly influence the TTP and MTT maps, while no such detrimental effects have been reported for CBF analysis.…”
Section: Discussionsupporting
confidence: 93%
“…From a methodologic point of view, we excluded the transition parameters (TTP and MTT) from our perfusion analysis. Our findings were in line with those of Förster et al, 32 who demonstrated that perfusion abnormalities in patients with MwA are predominantly substantiated by CBF and CBV changes. TTP analysis of the cerebellar hemispheres is hampered by variant vertebral artery configurations that directly influence the TTP and MTT maps, while no such detrimental effects have been reported for CBF analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the time course of CBF alterations did not appear to be linked with the persistence of aura symptoms, neither with the persistence of cephalalgia at the time of scanning in our cohort. These findings are in line with previously published works regarding CBF evolution obtained by positron emission tomography MRI or dynamic susceptibility perfusion‐weighted imaging during migraine with aura episodes that suggest that a typical episode begins with decreased regional flows during aura, which eventually increase significantly when the headaches appear. Moreover, our results add to those findings, enlightening the critical effect of the delay between onset and MRI, which seems to be more relevant than the symptoms at the time of imaging study.…”
Section: Discussionsupporting
confidence: 92%
“…Discussion.— Aura can persist beyond 4 h in 5% of MWA episodes and brain imaging may sometimes be required in order to properly exclude alternative diagnoses. During the initial phase of a migraine aura, hypo‐perfusion can typically be detected, occasionally extending over multiple vascular territories . A delayed hyper‐perfusion, detectable several hours after the beginning of the migraine and potentially persisting after resolution of the aura, has also been reported .…”
mentioning
confidence: 99%